Lexical input to young children from extremely poor communities in argentina: Effects of a home literacy program - Rosemberg, Celia Renata (2011)
The study analyzes the lexical properties of the linguistic context that children from marginalized urban neighborhoods from Buenos Aires, Argentina, are exposed to in the literacy situations generated by an at-home early literacy program. The analysis is focused on the comparison of the vocabulary that these children are exposed to daily with the characteristics of the lexical surround in the literacy settings induced by the implementation of the program. Results showed that literacy situations provided children with an enriched lexical input: a higher amount of word tokens and word types, and more unfamiliar words that represented phenomena, properties or actions not directly observable.